Regulatory T Cells Suppress Effector T Cell Proliferation by Limiting Division Destiny - Dowling, Mark R.; Kan, Andrey; Heinzel, Susanne; Marchingo, Julia M.; Hodgkin, Philip D.; Hawkins, Edwin D. (Frontiers in Immunology, 2018)
Understanding how the strength of an effector T cell response is regulated is a fundamental problem in immunology with implications for immunity to pathogens, autoimmunity and immunotherapy. The initial magnitude of the T cell response is determined by the sum of independent signals from antigen, co-stimulation and cytokines. By applying quantitative methods, the contribution of each signal to the number of divisions T cells undergo (division destiny) can be measured, and the resultant exponential increase in response magnitude accurately calculated. CD4+CD25+Foxp3+ regulatory T cells (Tregs) suppress self-reactive T cell responses and limit pathogen-directed immune responses before bystander damage occurs. Using a quantitative modelling framework to measure T cell signal integration and response, we show that Tregs modulate division destiny, rather than directly increasing the rate of death or delaying interdivision times. The quantitative effect of Tregs could be mimicked by modulating the availability of stimulatory co-stimuli and cytokines or through the addition of inhibitory signals. Thus, our analysis illustrates the primary effect of Tregs on the magnitude of effector T cell responses is mediated by modifying division destiny and survival of responding cell populations.